Review of lean manufacturing with IR4.0 in automotive industry - Dara, Affydah; A. N. M., Rose; M. F. F., Ab Rashid; N. M. Z., Nik Mohamed (IOP Publishing, 2021)
This paper aims to study the possibility of integration between Lean Manufacturing (LM) and Industrial Revolutions 4.0 (IR4.0). LM is generally known and acknowledged as a feasible system in the industrial sector. However, a new paradigm of IR4.0 has influenced manufacturers to look further into how LM could be implemented and adopted. It drives the integration of an intelligent factory to control machines, humans, products, and cloud solutions along the value chain. Manufacturers, especially in the automotive industry such as Toyota Company, have been using lean concepts and methods for so many years to eliminate wastes, reduce operational costs, and improve production performance. By integrating LM with IR4.0, the manufacturers could enhance productivity and quality by using the implementation chain. Besides, it enables self-management operational processes that could ensure the customer's quality of production.